Summer of the Arts : 19 July 2024 – 26 January 2025 - Bartana, Yael; Halbouni, Manaf; Melhus, Bjørn (Staatsgalerie Stuttgart, 2024)
The interdisciplinary cooperation project »Summer of the Arts« showed works by the 2022/2023 and 2023/2024 recipients of the Villa Massimo’s German Rome Prize in eight institutions in Stuttgart. The Staatsgalerie Stuttgart presented the art created by Yael Bartana, Manaf Halbouni, and Bjørn Melhus during their stays in Rome in dialogue with works from the Staatsgalerie collection.